The Effect of Fermentation on the Characteristics and Antioxidant Activity of Wuluh Starfruit Leaf Kombucha Tea (Avverhoa bilimbi Linn.) - Rosyada, Fanny Fajrin Aulia; Agustina, Eva; Faizah, Hanik (Indonesian Journal of Chemical Research, 2023)
Kombucha is a fermented drink that provides health effects. Wuluh starfruit leaves are one of the ingredients that can be used in making kombucha. This study was conducted to determine the effect of fermentation time on the physical, chemical, and antioxidant characteristics of wuluh starfruit leaf kombucha tea (Avverhoa bilimbi Linn.). This research is an experimental study with a completely randomized design (CRD) consisting of 4 treatments. Kombucha wuluh starfruit leaves are made with a fermentation time of 0, 4 8, and 12 days. The physical characteristics tested include an organoleptic test of scent, color, and taste. The chemical characteristics tested include pH, levels of titrated acids (tta), phenolic, and alcohols. The antioxidant activity is known by determining the value of IC50. Organoleptic, pH, tat, and phenolic assessment data were statistically analyzed using Kruskal Wallis and Mann Whitney. Alcohol content and antioxidant activity were analyzed descriptively. The best result of physical, and chemical characteristics and antioxidant activity are on the 12th day of fermentation with a pH of 3, TTA 0.11 0.070%, phenolic 87.33 1.140 mg/ml GAE and alcohol of 0.41% with an IC50 value of 3.65 ppm.